PEMBERDAYAAN MASYARAKAT MELALUI WAKAF TERNAK AYAM BERDASARKAN ASPEK KELEMBAGAAN DAN MODAL SOSIAL PADA YAYASAN AL ISLAM KOTA PAYAKUMBUH - Muhamad Fadhil; Ahmad Wira, Helmalia, Romy Yunika Putra (BORJUIS: JURNAL OF ECONOMY, 2025)
Community empowerment is an effort carried out through a series of activities to strengthen the empowerment of a weak group in society to achieve a better life. Community empowerment is seen through the institutional aspects of waqf, social capital and productive waqf. The aim of this research is to obtain evidence of community empowerment through chicken livestock waqf based on institutional aspects of waqf and social capital at the Al Islam Foundation in Payakumbuh City. This research uses quantitative methods with the type of field research. Researchers used primary data through observations and questionnaries with total sampling techniques. This research used 35 samples for questionnaires which were analyzed using the SEM – PLS method. The results obtained in this research are that institutions do not have a significant influence on productive waqf, while social capital has a significant influence on productive waqf. Waqf institutions have a significant influence on community empowerment and social capital has a significant influence on community empowerment. The influence of waqf institutions on community empowerment through productive waqf for chicken farming does not have a significant effect. The influence of social capital on community empowerment through productive chicken farming endowments does not have a significant effect. The influence of productive waqf on community empowerment does not have a significant effect.